If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = 3X + 4 + -1(2X + -4) Reorder the terms: 2 = 3X + 4 + -1(-4 + 2X) 2 = 3X + 4 + (-4 * -1 + 2X * -1) 2 = 3X + 4 + (4 + -2X) Reorder the terms: 2 = 4 + 4 + 3X + -2X Combine like terms: 4 + 4 = 8 2 = 8 + 3X + -2X Combine like terms: 3X + -2X = 1X 2 = 8 + 1X Solving 2 = 8 + 1X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1X' to each side of the equation. 2 + -1X = 8 + 1X + -1X Combine like terms: 1X + -1X = 0 2 + -1X = 8 + 0 2 + -1X = 8 Add '-2' to each side of the equation. 2 + -2 + -1X = 8 + -2 Combine like terms: 2 + -2 = 0 0 + -1X = 8 + -2 -1X = 8 + -2 Combine like terms: 8 + -2 = 6 -1X = 6 Divide each side by '-1'. X = -6 Simplifying X = -6
| 4(x+3)-4=8(.5+1) | | 7x+10=11x+6 | | x+3=224x^2 | | 12+4x-7x=x-4 | | 5x^2+10=-4x | | 8-4x+4y=2x+6 | | 8x^2+21x-45=0 | | 5-7x+4=9-x | | -54=9-x | | x+2+x+4-x=22 | | -6n+6=-5n | | 14=2(n+8) | | x^2+12x+36=25equation | | f=(850)(3) | | 4x-6=2x-3 | | -2y(y-4)=20-2y-12 | | -7x+5x+5=2x+1 | | -10*5x*(-8)= | | -4u+9=5u | | 3(4c-1)-5=10c+6 | | f(x)=-3x^2+18x-32 | | -6+8y=9y | | y=x^3+4x^2-5x | | 3x+2=7x-18 | | 9m+12=3m-24 | | 3k=-3k+12 | | 3x+2x=7x-18 | | (7+3x)-(2x+5)=8 | | -4-3k=-3k+8 | | x+5-6=1 | | 31+3y-12=15y-9-5y | | 9n=-2n+35 |